Use of Cardiopulmonary Bypass for Management of Massive Air Embolism During Hysteroscopic Metroplasty - Amirghofran, Ahmad Ali (J Extra Corpor Technol, 2016)
The patient was a 32-year-old woman who presented with infertility secondary to uterine didelphys. Hysteroscopic metroplasty was chosen as the corrective surgical procedure for this anatomical defect. During the surgical repair, the patient developed a massive air embolism (MAE) leading to hypotension, arrhythmia, and cardiogenic shock. Resuscitation was started by placing the patient in the right-side up position, and emplacement of central venous catheter, but it was unsuccessful. The decision was then made to bypass the patient's cardiopulmonary system to effectively treat the MAE. Cannulation was done via femoral vein and artery. During cardiopulmonary bypass (CPB), the MAE was quickly eliminated, oxygen saturation was normalized, and the patient was hemodynamically stabilized. The surgical repair was successfully completed and the patient was decannulated and recovered without any incident.